Ensiling Legume with Cereal Fodder Influences Quality of Silage Mixtures - Goyal, Meenakshi; Tiwana, U.S. (Indian Journal of Animal Nutrition, 2018)
This study was conducted to determine the fermentation characteristics and nutritive value of corn (Zea mays L.) + cow pea (Vigna ungiculata L.) and oats (Avena sativa L.) + alfalfa (Medicago sativa L.) silages. The corn-cowpea and oats-alfalfa mixtures were ensiled separately in the ratio of 100: 0 (A), 75: 25 (B), 50: 50 (C), 25: 75 (D) and 0: 100 (E) of grass and legume in each case. The fodder mixtures were ensiled in vacuumed plastic bags for 45 days at room temperature. The addition of cowpea in corn or alfalfa in oats had significant effect (P